The contribution of direct energy use for livestock breeding to the greenhouse gases emissions of Cyprus - Florides, Georgios A.; Kythreotou, Nicoletta; Tassou, Savvas A. (My University, 2011)
This paper presents a methodology for the estimation of the contribution of direct energy use to the greenhouse gases emissions of cattle, pig and poultry breeding in Cyprus. The energy consumption was estimated using the factors of 2034 MJ/cow, 2182 MJ/sow and 0.002797 MJ/bird. The greenhouse gases emissions for each animal species and energy source were estimated using emission factor of each greenhouse gas according to fuel type as proposed by the IPCC 2006 guidelines and for electricity according to national verified data from the Electricity Authority of Cyprus. Livestock breeding in Cyprus consumes electricity, diesel oil and LPG. The results obtained, show that the emissions from energy use in livestock breeding contribute 16% to the total agricultural energy emissions. Agricultural energy emissions contribute 0.7% to the total energy greenhouse gases (GHG) emissions. The three species of animal considered contribute 3% to their total livestock breeding emissions when compared with enteric fermentation and manure management, of which 2.6% is CO2. These results agree with the findings in available literature. The contribution of direct energy use in the greenhouse gases emissions of livestock breeding could be further examined with the influence of anaerobic digestion to the emissions
Keywords: Cyprus; Energy; Cyprus; Emissions; Pigs; Poultry